A new species of Aphantaulax Simon, 1878 from Thailand, with the first description of the male of A. fasciata Kulczyński, 1911 (Araneae, Gnaphosidae) - Pakawin Dankittipakul (2018)
A new species of the gnaphosid genus Aphantaulax Simon, 1878, A. rostrata n. sp., is described from Chaiyaphum Province, Thailand. The male of A. fasciata Kulczyński, 1911 is described here for the first time, based on specimens collected from deciduous forests of north-eastern Thailand. This discovery expands the distribution range of the species northwards.